O futebol como meio para construção do processo de cidadania de adolescentes de classes populares do Município de Niterói - Vianna, Aurélio Pitanga (2006)
The forms for the which the education has been approached in the Brazilian society have been varying historically, evidencing the idea proposed in this dissertation that the education is a socialization process, in other words, that it integrates the individuals in the social context and, for that reason, it varies according to the time and the half. Although supposing that the education doesn't just integrate the individual into the social way, but it also provides him/her a larger autonomy capacity and, for that reason, of interference in the social way, it is relevant to show that the education always has an importance eminently social, although that subject assumes different connotations through the history. The intention here is of discussing the contemporary approach given to the education in the Brazilian society, above all to the education ideas as promoter of competitiveness and of social citizenship, showing, likewise, as the sport it can be seen starting from this education conception and as it is related to certain transformations of the Brazilian society, in which are included the combat process the social exclusion and the poverty. The present study had as methodology the empiric and experimental research of field, where the researcher was made part of the process and observer at the same time. It was taken as model for practical evaluation of the presented theory the project Education & Ball.